Single-cell RNA sequencing reveals a B cell-related immunosuppressive landscape and a potential suppressor in hepatocellular carcinoma - Wenhao Hou; Jiaqi Jiang; Liyuan Zhu; Hongwei Xu; Lihui Zhu (Journal of Translational Medicine)
Abstract Background The sophisticated tumour microenvironment is responsible for the malignant progression and poor prognosis of hepatocellular carcinoma (HCC). Discovering new therapeutic targets is desired for the preferable treatment of HCC patients. Methods To characterize the HCC microenvironment, the single-cell transcriptomes of HCC tissues and corresponding noncancerous tissues were analysed. Differentially expressed genes (DEGs), enriched pathways and subgroups were analysed in B cells. Moreover, heterogeneity between malignant and normal hepatocytes was further investigated, which revealed potential biomarkers for HCC progression. The candidate biomarkers were further explored in datasets from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. Serum amyloid A2 (SAA2) was detected and further validated in HCC tissues by immunohistochemistry (IHC) and western blot analysis. The biological roles of SAA2 were further investigated in HCC cells. Results The number of B cells in HCC tissues was significantly lower than that in noncancerous tissues, which may result in an immunosuppressive status of the HCC microenvironment. Differentially expressed genes (DEGs) and functional enrichment analysis revealed that B cells might participate in the immunosuppression of HCC by regulating lipid metabolism. Analysis on B cell subgroups demonstrated Naïve B cells were significantly reduced in HCC tissues compared with noncancerous tissues, which indicated that Naïve B cells might be pivotal in the B cell-related immunosuppressive landscape in HCC. Further analysis of hepatocytes revealed highly expressed genes in normal hepatocytes derived from noncancerous liver tissues, which were validated in datasets from The Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx) databases. Interestingly, serum amyloid A2 (SAA2) was highly expressed in normal liver tissues compared with HCC tissues. The results were validated in clinical HCC samples by immunohistochemistry (IHC) and western blot assays. Moreover, investigations in HCC cells revealed that SAA2 acted as a tumour suppressor in HCC progression. Conclusions Taken together, the present findings elucidated the B cell-related immunosuppressive landscape in HCC and identified SAA2 as a novel suppressor in HCC, providing a better understanding of the HCC landscape and suggesting a promising therapeutic target for HCC patients.